PEMURNIAN MINYAK GENOAK ( Acorus calamus ) ASAL PULAU TIMOR MENGGUNAKAN DISTILASI PENGURANGAN TEKANAN - Rensy A. Henci; Reinner I Lerrick; Theo Da Cunha (Saintek Lahan Kering, 2020)
A research about Asaron oil purification produced over Stahl distillation has been done. This research was conducted by distillation of genoak’s roots, rhizomes and laeves whilist the purification was carried out through reduced pressure distillation. A yellowish oil was yield respectively 1,83 gram from the roots and rhizomes and 1,26 gram from laeves which the was revealed as 90,49% pure of asaron confirmed by GC-MS, 1H-NMR and FT-IR analysis.